STUDENTS’ PERCEPTIONS ON THE USE OF ONLINE ROLE-PLAYING GAMES TO ENHANCE THEIR VOCABULARY KNOWLEDGE - Tiara Sonita; Nurlaily Nurlaily; Hilarius Raditya Priambada (IKIP Siliwangi, 2024)
Nowadays, teaching and learning activities are not only in the classroom. There are many resources from the internet that can be used as learning tools outside the classroom. One of the activities is playing online games. Even though it sounds like something usual, online games can help students to improve their English skills, especially their vocabulary. Online games provide various vocabulary to the students and help them to enhance their vocabulary knowledge from the in-game facilities. This research aimed to explore students’ perceptions towards RPG online games enhancing their vocabulary knowledge. This research’s results will find out; 1) How the students perceive the online RPGs in enhancing students’ vocabulary knowledge? and 2) How do the students enhance their vocabulary knowledge other than online RPGs? The participants of this research are students from Universitas Internasional Batam who played any online role-playing games. By using descriptive quantitative, this research will gather the data via questionnaire. This research gets positive feedback from the participants. They are agreed that online RPGs is helping them to enhance their vocabulary knowledge from in-game features. There are also some of other apps that participants’ use to enhance their vocabulary knowledge. Researcher hopes this research can give new insights of online games to be used as a learning media for both students and teachers.